2009
DOI: 10.1634/stemcells.2007-1018
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for the Derivation of Putative Primordial Germ Cells and Sertoli Cells from Human Embryonic Stem Cells

Abstract: Using human embryonic stem cells (hESCs), we describe a novel method for the rapid derivation and enrichment of cells that are comparable to primordial germ cells (PGCs) and Sertoli cells. The methodology described is based on modest changes to the growth conditions commonly used to expand hESCs and does not require genetic manipulation or complex three-dimensional culture. Remarkably, we have determined that simply reducing the size of cultured ESC colonies and manipulating the number of feeding cycles, resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
121
0
3

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 53 publications
(99 reference statements)
4
121
0
3
Order By: Relevance
“…The efficiency of differentiation from ES or iPS cells into haploid male germ cells is generally reported to be low. [14][15][16][17][18][19][20][21][22][23][24] Although there is no evidence for the speculation that this efficiency might be higher using AFS cells, to our opinion, the here reviewed knowledge warrants testing this new stem cell type for their usability for the in vitro investigation of sperm production (Figure 1).…”
Section: Amniotic Fluid Stem (Afs) Cells Could Be a Useful Tool To Stmentioning
confidence: 88%
“…The efficiency of differentiation from ES or iPS cells into haploid male germ cells is generally reported to be low. [14][15][16][17][18][19][20][21][22][23][24] Although there is no evidence for the speculation that this efficiency might be higher using AFS cells, to our opinion, the here reviewed knowledge warrants testing this new stem cell type for their usability for the in vitro investigation of sperm production (Figure 1).…”
Section: Amniotic Fluid Stem (Afs) Cells Could Be a Useful Tool To Stmentioning
confidence: 88%
“…It was shown that increasing BMP4 concentration from 10 ng/ml to 100 ng/ml significantly improved VASA expression, especially upon addition of BMP4 together with BMP7 and BMP8b (Kee et al 2006). Other groups also demonstrated a culture-enrichment strategy by sorting for cells positive for early PGC markers such as cKIT, SSEA1 and CXCR4 (Tilgner et al 2008;Bucay et al 2009;Park et al 2009). Further differentiation of only this selected cell population led to increased germ cell gene expression (Tilgner et al 2008;Bucay et al 2009;Park et al 2009).…”
Section: Embryonic Stem Cells Derived Germ Cells and Gametesmentioning
confidence: 99%
“…Certains marqueurs commencent à être reconnus comme incontournables pour l'établissement du phénotype des CGP : ainsi PRDM1, sous le contrôle de la signalisation BMP/SMAD, est essentiel à l'orientation des cellules CSE vers une identité CGP chez la souris comme chez l'homme. Chez l'humain, deux équipes ont mis en évidence les transcrits PRDM1 dans des CGP obtenues à partir de hCSE par différents protocoles qui seront détaillés ci-après [7,8] TRA-1-60 [7,16,22] TRA-1-81…”
Section: Obtention De Cellules Germinales Primordiales Et De Gonocyteunclassified
“…[5, 7,13,16,19,22,24,25,27] Cellules Sertoli, cellules Leydig, cellules de la granulosa, cellules de la thèque…”
Section: V-kit Hardy-zuckerman 4 Feline Sarcoma Viral Oncogene Homologunclassified
See 1 more Smart Citation